KONTEKS SISTEM SEKUNDER DI SITUS CABEAN KUNTI, BOYOLALI (PANDANGAN MASYARAKAT DAN DAMPAKNYA PADA KELESTARIAN SITUS) - Sugeng Riyanto (BRIN, 2005)
The secondary system context is the BCB (heritage) that applies in today's society's life system. This phenomenon becomes interesting because the